2010
DOI: 10.1021/jo101543q
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-Catalyzed Addition of Carboxylic Acids to Alkynes

Abstract: Au(I)-catalyzed hydroacyloxylation of alkynes with carboxylic acids is described. PPh3AuCl/AgPF6 catalyst affords the Markonikov addition products, whereas PPh3AuCl/AgOTf catalyst gives the more stable isomerized products via the Markonikov products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…This transformation has been previously realized using 5 mol % Ph 3 PAuCl/AgPF 6 with catalyst TONs up to 18(34), and the best catalyst TON (i.e., 124) of this type of reaction was achieved via Ru catalysis. (35) Importantly, the alkenyl esters products possess mildly activated acyl groups and are versatile substrates of broad synthetic utilities.…”
Section: Resultsmentioning
confidence: 94%
“…This transformation has been previously realized using 5 mol % Ph 3 PAuCl/AgPF 6 with catalyst TONs up to 18(34), and the best catalyst TON (i.e., 124) of this type of reaction was achieved via Ru catalysis. (35) Importantly, the alkenyl esters products possess mildly activated acyl groups and are versatile substrates of broad synthetic utilities.…”
Section: Resultsmentioning
confidence: 94%
“…A more general study was published by Chary and Kim in 2010 employing the catalytic system [AuCl(PPh3)]/AgPF6 (5 mol%). 88 Thus, they found that, in toluene at 60-110 °C, the in situ formed [Au(PPh3)] + cation cleanly and efficiently catalyzes the anti-addition of different carboxylic acids to both terminal and internal alkynes. With regard to the latter, the results obtained in the four reactions covered by Chary and Kim are shown in Scheme 12.…”
Section: Gold-based Catalystsmentioning
confidence: 99%
“…No general protocol for vinyl ether synthesis using gold has been reported to date [17]. Nevertheless, there have been examples regarding the intermolecular addition of carboxylic acids [1920], phenols [2122] as well as phosphoric acids [2325] to alkynes. In this context, we report a gold(I)-catalyzed O-vinylation of 1,3-diketones with unactivated alkynes at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%